Understanding the changes in construction project managers’ competences through resume data mining - Zheng, Junping; Qiang, Maoshan (Journal of Civil Engineering and Management, 2022)
Construction project managers (CPMs) play a crucial role in project management. Using nearly 250,000 online resumes, this study aims to identify the major aspects and explore the prevalence trend of competences required by CPMs in real work. A data mining approach, Dynamic Topic Model (DTM), was adopted and ten aspects of CPMs’ competences are disclosed. The results of Mann-Kendall tests suggest that among technical skills, work experience and the ability of information technology application are gaining increasing attention rather than professional skill. Moreover, human skills, key managerial competences (i.e., procurement management, risk management and site management) and organizational skill are highlighted. Theoretically, the results provide a systematic review on the real-world competence requirements and their changing trends for CPMs. In practice, these findings can not only be utilized to help students in relevant major and practitioners benchmark their own competences with real-world requirements, but also assist construction firms in formulating more informed talent strategies.